Pengaruh Price Earning Ratio, Debt To Equity Ratio dan Return On Asset terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bei - Wongsosudono, Corinna; Karo, Mira Br (JURNAL MUTIARA AKUNTANSI, 2021)
This study aims to analyze the effect of Price Earning Ratio, Debt to Equity Ratio and Return On Asset on Stock Price in manufacturing companies listed in BEI. The variables tested in this study are independent variabels consisting of Price Earning Ratio, Debt to Equity Ratio and Return On Asset and dependent variable is the Stock Price. The population in this study is the food and beverage sub-sector manufacturing companies that registered in BEI 2016-2018, as many as 19 companies. The number of samples in this study are 10 companies, the data used in this study are secondary data obtained from the site www.idx.co.id and sample selection using purposive sampling method. The data analysis technique used is multiple linear regression of a significance level of 5%. The conclusion of this study is that the Price Earning Ratio, and Debt to Equity Ratio do not have a partial effect on Stock Price, while Return On Asset have a partial effect on Stock Price. Based on simultaneous tests show that the Price Earning Ratio, Debt to Equity Ratio and Return On Asset affect the Stock Price.